Exploring the link between dietary inflammatory index and NAFLD through a structural equation modeling approach - Azam Doustmohammadian; Farhad Zamani; James R. Hébert; Maziar Moradi-Lakeh; Sepideh Esfandyiari; Bahareh Amirkalali; Nima Motamed; Mansooreh Maadi; Sherry Price; Esmaeel Gholizadeh; Hossein Ajdarkosh (Journal of Health, Population and Nutrition)
Abstract Nonalcoholic fatty liver disease (NAFLD) or metabolic dysfunction–associated steatotic liver disease (MASLD) is a significant global public health dilemma with wide-ranging social and economic implications. Diet and lifestyle modifications remain essential components of NAFLD management. The current study investigated the association between diet-related inflammation and NAFLD among 3110 Iranian adults participating in the Amol Cohort Study (AmolCS), employing the Structural Equation Modeling (SEM) approach.The inflammatory potential of the diet was quantified using an energy-adjusted dietary index (E-DII) score. Findings showed that in the total sample and separately in males, the E-DII score had a significant effect on NAFLD, with mediation through hypertension (βstandardized = 0.16, and 0.13, p < 0.001, respectively) and c-reactive protein (CRP) (βstandardized = 0.07, and 0.07, p < 0.001, respectively). In the total sample and separately in females, the E-DII score significantly affected NAFLD, with mediation through diabetes (βstandardized = 0.06, p < 0.001, and 0.07, p = 0.006, respectively). In full and both gender-specific models, dyslipidemia was a risk factor for NAFLD and partially mediated the effect of hypertension on NAFLD. The current study concluded a mediated association between dietary inflammation and NAFLD through hypertension, CRP, diabetes, and dyslipidemia, suggesting further longitudinal studies, especially in high-risk populations. These findings underscore the complex interplay between diet, inflammation, and NAFLD in Iranian adults.